Flexible and stretchable 3D printed passive UHF RFID tag. Issue 15 (1st July 2017) - Rizwan, M.; Khan, M.W.A.; He, H.; Virkki, J.; Sydänheimo, L.; Ukkonen, L.
Abstract : The fabrication and analysis of a flexible and stretchable 3D printed passive ultra‐high frequency (UHF) radio‐frequency identification (RFID) tag are presented. The tag is fabricated on a flexible 3D printed Ninjaflex substrate and the conductive part of the tag consists of stretchable silver conductive paste dispensed with direct write method. The details of the 3D printing of the substrate, the characterisation of the substrate material at the UHF band, the direct write dispensing of the tag antenna, and the simulation and wireless measurement results of the fabricated tag are outlined. Moreover, to verify the flexibility and stretchability of the tag, strain reliability results of the tag are presented. Measurement results show that initially the manufactured tag achieves a 10.6 m read range. After 100 times of harsh stretching, the read range is still 7.4 m. Overall, the performance of the tag is robust and concludes that the fabrication methodology can be used in the manufacturing of RFID tags for future identification and sensing applications.